Biliary-intestinal anastomosis leads to alterations in intestinal flora and its flora metabolites and increases the risk of long-term postoperative complications: a case-control study - Li, Baicheng; Chen, Zhao; Wang, Guangzhi; Chen, Yuzhuo; Hou, Xingdong; Lu, Bowei; Ning, Shili (Frontiers in Microbiology, 2025)
ObjectivePancreaticoduodenectomy (PD) is a major surgical intervention that encompasses the resection of multiple organs and the reconstruction of the digestive tract, with reconstructive procedures including pancreatico-enteric, bilioenteric, and gastroenteric anastomoses. Prior research has documented a high incidence of long-term complications following PD, which significantly impact patient prognosis and survival, however, the underlying mechanisms remain elusive. Evidence from previous studies suggests that biliary-intestinal anastomosis modifies biliary tract anatomy, altering bile flow into the gut and potentially affecting the gut microbiota and its metabolites. Given the close association between biliary tract infections and alterations in gut microbiota, we hypothesize that changes in intestinal flora and its metabolites post-PD may be a critical factor in the development of long-term complications. The objective of this study is to investigate whether biliary-intestinal anastomosis during PD induces changes in the intestinal microbiota and its metabolites, which in turn may increase the risk of long-term postoperative complications.MethodsThis study included 17 patients who underwent the procedure (group T) and 20 sex- and age-matched controls who did not (group N), patients in group T were stratified into those with (complication group) and without (non-complication group) long-term postoperative complications. Faecal samples were collected from all subjects and DNA was extracted from the samples using 16S rRNA gene sequencing to analyse the composition of the faecal flora and detect flora metabolites.Results1. Alpha diversity analysis of the two sample groups indicated a trend towards lower microbial abundance in Group T relative to Group N, however, no significant differences were observed in the Shannon and Simpson diversity indices. 2. At the genus level, Group T patients exhibited markedly higher levels of Escherichia-Shigella, Veillonella, and Enterobacter, while showing significantly lower abundance of Blautia and Bifidobacterium compared to Group N subjects. Analysis of Spearman’s correlation and degree of correlation between genera showed a significant negative correlation between Escherichia shigella and Blautia. Veillonella showed a significant positive correlation with both Escherichia shigella and Enterobacter. In addition, Blautia and Bifidobacterium showed a significant positive correlation with each other. 3. Subsequent comparative analysis of the bacterial flora between the complication and non-complication groups revealed a significantly elevated abundance of Escherichia-Shigella in the complication group as compared to the non-complication group. 4. Faecal metabolomic analysis revealed that L-palmitoylcarnitine, arachidic acid and PG 13:0_15:0 were significantly increased in the T group compared to the N group, whereas 3-isopropylmalic acid was significantly decreased in the T group. 5. KEGG pathway analysis identified nine crucial metabolic pathways associated with these microbial shifts: alterations in starch and sucrose metabolism, steroid hormone biosynthesis, caffeine metabolism, the citric acid cycle, riboflavin metabolism, sulfur metabolism, and the biosynthesis of valine, leucine, and isoleucine, as well as pyruvate metabolism and ABC transporter protein pathways.Conclusion1. The biliary-intestinal anastomosis, which is performed as part of a pancreaticoduodenectomy, induces significant shifts in the intestinal flora. 2. Increased abundance of Escherichia-Shigella may promote long-term complications after biliary-intestinal anastomosis. 3. Biliary-intestinal anastomosis leads to alterations in the metabolites of the patient’s intestinal flora. 4. Intestinal flora and their metabolites in patients after biliary-intestinal anastomosis may contribute to the development of long-term complications through nine metabolic pathways.